Speech(lessness), Negative Pleasure, and the Sublime Objects of Suburbia in Ben Lerner’s The Topeka School - Nikolai Wansart ([sic])
Lerner’s The Topeka School references “the twenty-four-hour news cycle, Twitter storms, algorithmic trading,” (24) as a version of the debate strategy of the spread in the post-truth United States. In a similar way, the incessant and supernumerary presence of suburban objects in the novel functions as a spread the characters continuously have to face. Linking the spread and the sublime, this essay examines how the novel intertwines the characters’ responses to their suburban home with their subsequent futures on their way into the Trumpian post-truth age. Informed by the Kantian sublime, it shows how the sublime of the spread denies negative pleasure as the denouement of the threat of the sublime. The essay develops the argument that Lerner’s novel frames the ability to linguistically respond to the paradoxically placing and displacing effect of the sublime of the spread as a tool that on the one hand can help them navigate their 1990s-suburban life, but on the other hand also foreshadows their response to further paradoxical displacement in the post-truth era.